Does tinnitus amplify the effects of healthy eating patterns and physical activity on the sleep disturbance or sleep insufficiency, based on the case study of NHANES survey in the United States - Chen, Jia; Zou, Wujun; Li, Hao; Luo, Yu; Lu, Kaifu; Yi, Xuelian; Li, Hong; Shi, Zhu; Meng, Juan (Frontiers in Nutrition, 2024)
Exploring whether the presence of tinnitus amplifies the effects of an individual's dietary patterns and physical activity on sleep disturbance or sleep insufficiency.This study extracted data from the five National Health and Nutrition Examination Surveys (NHANES) between 2009 and 2018, including individuals who had undergone complete questionnaires on tinnitus, dietary habits, physical activity, and sleep. Multivariate logistic regression, restricted cubic spline (RCS) and subgroup analyses were conducted to explore the associations of dietary habits, physical activity, and tinnitus with sleep disturbance and sleep insufficiency.A total of 7,440 participants were enrolled in this study, of whom 1,795 participants were evaluated as sleep disturbance (24.13%), and 2,281 were sleep insufficiency (30.66%). With adjusting confounding factors of demographic and socioeconomic variables, among overall population, participants with tinnitus showed a significantly increased risk of sleep disturbance (adjusted odds ratio (aOR) = 2.08, 95% confidence interval (CI): 1.83 -2.36), and sleep insufficiency (aOR = 1.31, 95% CI: 1.15 -1.49).Poor dietary habits also increased the risk of sleep disturbance (aOR = 1.08, 95% CI:1.04 -1.12), as does lack of physical activity (aOR = 1.14, 95% CI: 1.03 -1.27); but neither exposure factors significantly increased the risk of sleep insufficiency. The nonlinear trend analyses of RCS found that the influence of exposure factors on sleep disturbance experiencing a steady or small decline trend after rising. In addition, the results of the subgroup analysis showed that in tinnitus patients, poor dietary habits and lack of physical activity both significantly increased the risk of sleep disturbance, and poor dietary habits also increased the risk of sleep insufficiency remarkable, but lack of physical activity did not. In healthy participants, poor dietary habits were only significantly associated the sleep disturbance, while lack of physical inactivity even had a protective effect against sleep insufficiency.Compared to the general population, tinnitus significantly amplified the effects of poor dietary patterns and physical inactivity on sleep disturbance and sleep insufficiency. For tinnitus patients, adjusting a healthy diet and increasing exercise could more effectively promote their sleep health.